Continuous control of surface-plasmon excitation wavelengths using nanomechanically stretched subwavelength grating. (8th January 2016) - Honma, Hiroaki; Takahashi, Kazuhiro; Ishida, Makoto; Sawada, Kazuaki
Abstract: We report a new method for continuously controlling surface-plasmon (SP) excitation wavelengths using a nanomechanically stretched metal subwavelength grating. An aluminum subwavelength grating is integrated with electrostatic comb-drive actuators to expand the metal subwavelength period, which allows continuous control of the dependent excitation wavelength. We successfully demonstrated that the excitation wavelength over the 542–668 nm range varies continuously with the square of the applied voltage, which agrees well with the theory of electrostatic actuation. This new modulation method can provide the functions of readjustment and continuous tuning for SP-based devices.